Water use and wood productivity of Eucalyptus grandis plantations: effects of management, water supply and soil texture - Deus Junior, José Carlos de (2019)
Water availability is a strategy resource for forest plantation. Many authorities and researches are concerned about the water use and the impact of forest plantation. Water use and water use efficiency have been measuring in all over the world. High productivity of Eucalyptus sp plantation are depend of environmental resources such water, nutrients, light and also genotype resource efficiency. High water use is also associated with high productivity and water use efficiency. Many reports were published about water use in eucalyptus plantation. Water use might vary among 1100 mm to 1300 mm for eucalyptus plantation. Climate conditions, soil characteristics and forest management might influence water use. Currently, studies aim to understand hydrology cycle at the leaf, trees and on landscape scale. Previous studies showed that K fertilizer increase water demand. Leaf biomass and LAI also increase due to K fertilizer application, which suggest increase in water use. Eucalyptus forest plantation may also decrease water discharge in catchment, which might decrease water availability in local scale. However, transpiration varied within soil moisture, precipitation, temperature, atmosphere conditions, fertilizer application, genotype and latitude. The main objective of forest managers was often find a technique regime which forester may use to achieve the target growth rate. Nowadays, it is important to manage the forest taking to account local resource supply, local climate condition and resource availability. These strategies might increase the sustainability of forest plantation. Measurement of physiological functioning might help forests manager to understand the growth response of our forest as result of climate condition and also planning new strategies to increase forest sustainability.